2020
DOI: 10.29412/res.wp.2020.19
|View full text |Cite
|
Sign up to set email alerts
|

Do Lenders Still Discriminate? A Robust Approach for Assessing Differences in Menus

Abstract: We use a new methodology to assess mortgage pricing discrimination faced by minority borrowers. We identify a "menu problem" that comes from the multidimensional nature of mortgage pricing: When getting a mortgage, borrowers can choose to avoid closing costs and pay a high interest rate or contribute to closing costs to get a lower rate. While data on both dimensions of mortgage pricing are by now often available, intuitively attractive metrics of lender pricing discrimination used in the literature can lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Since the seminal study of Munnell et al (1996), this research has consistently shown that minorities exhibit lower mortgage approval rates and higher interest rates. This literature has identified several plausible sources of the racial disparities in this market, including information noise (Blattner and Nelson, 2021), discrimination (Bartlett et al, 2022;Bhutta and Hizmo, 2021;Zhang and Willen, 2021), and exposure to risky lenders (Bayer et al, 2018). However, these studies have rarely focused on minority-owned banks, except for Bostic (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal study of Munnell et al (1996), this research has consistently shown that minorities exhibit lower mortgage approval rates and higher interest rates. This literature has identified several plausible sources of the racial disparities in this market, including information noise (Blattner and Nelson, 2021), discrimination (Bartlett et al, 2022;Bhutta and Hizmo, 2021;Zhang and Willen, 2021), and exposure to risky lenders (Bayer et al, 2018). However, these studies have rarely focused on minority-owned banks, except for Bostic (2003).…”
Section: Introductionmentioning
confidence: 99%